Iranian medical students' E-learning continuance intention after end of COVID-19 pandemic - Hossein Ghalavand; Mahboobeh Momtazan; Saeed Jelvay; Seyed Hojjat Khatamifar; Zahra Heydarvand (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Coronavirus disease (COVID-19) pandemic caused the closure of many face-to-face classes in Iran's universities of medical sciences, so e-learning was adopted as the alternative method. This study aims to examine the medical students' perspectives on e-learning continuance intention. MATERIALS AND METHODS: In this quantitative study, the population included 1,453 students and the statistical sample size was determined to be 305 students using the Cochran formula. The participants were selected using stratified sampling method based on the field of study and the data were collected by e-learning evaluation questionnaire. The data were analyzed using SPSS 26.0 in addition to descriptive statistics. RESULTS: The results showed the mean perceived autonomy, perceived competence, and communication in e-learning, intrinsic motivation, information quality, e-learning applicability and students' satisfaction with e-learning courses were 2.61, 2.81, 2.91, 3.03, 2.98, 2.92, and 3.31, respectively. There was no significant correlation between the competence and applicability, user satisfaction and e-learning continuance intention. Moreover, e-learning continuance intention had the highest correlation with students' satisfaction (0.787) and information applicability (0.784), respectively. CONCLUSION: Medical students had a tendency to continue e-learning, even after controlling the COVID-19 outbreak, and health education policymakers can be of use in this opportunity to developing educational services.